2017
DOI: 10.1002/ccd.27370
|View full text |Cite
|
Sign up to set email alerts
|

The JUPITER registry: One‐year outcomes of transapical aortic valve implantation using a second generation transcatheter heart valve for aortic regurgitation

Abstract: The JenaValve overcomes technical challenges of TAVR in AR through a clipping mechanism. We report satisfactory outcomes of a multicenter registry using the JenaValve for predominant AR, as rate of THV embolization, residual AR and permanent pacemaker implantation was low. One-year results using the JenaValve for AR encourage its use for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 24 publications
2
32
1
1
Order By: Relevance
“…The initial search revealed a total of 5,208 potential articles. After exclusions, 19 reports remained for analysis (13 full texts , and 6 conference abstracts ). The PRISMA flow chart (Figure ) gives an overview of the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search revealed a total of 5,208 potential articles. After exclusions, 19 reports remained for analysis (13 full texts , and 6 conference abstracts ). The PRISMA flow chart (Figure ) gives an overview of the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…12) In addition, the feasibility of TAVI for patients with PAR was proven in several second-generation THV, including Evolut-R, 18) SAPIEN 3, 8) ACURATE neo, 9) Direct Flow Medical, 10) Lotus 11) et al The 1-year outcome of TAVI using a second-generation THV (J-Valve and Jenavalve) for PAR has been reported, and it presented a satisfactory outcome. 4,5,7) However, the long-term durability and efficiency of these devices were not demonstrated. Our study first reported the long-term follow-up of TAVI using J-Valve for PAR, and the dependable durability and Continuous variables were performed as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of transcatheter heart valve (THV) devices and the technique of TAVI procedure, the second-generation THV has revolutionized the interventional treatment for PAR. 4,5) There are multiple reports presenting the feasibility of transcatheter approach for the treatment of PAR, 4,[6][7][8][9][10][11] and second-generation devices associated with an excellent procedural success rate and favorable perioperative outcomes compared with first-generation THV. In second-generation devices, the advantage is more pronounced on the "on-label" THVs (J-Valve and JenaValve) than "off-label" THVs.…”
Section: Introductionmentioning
confidence: 99%
“…By now, only the JenaValve transcatheter heart valve (JenaValve Technology) and the J-Valve system (JC Medical) have been designed to address the morphological challenges in patients with AR, by providing a dedicated anchoring system in the aortic annulus in the absence of calcification. First clinical experiences reported a high procedural and device success rate for the JenaValve, leading to a CE Mark in Europe for the treatment of AR (38)(39)(40). In comparison to standard newer generation transcatheter heart valves, dedicated devices lead to a higher procedural success.…”
Section: Treatment Decision and Current Limitationsmentioning
confidence: 99%